COMPARISON OF RESULTS OF PULUT CORN STARCH MODIFICATION AND SORGUM STARCH BY ACID HYDROLYSIS METHOD - Isra, Muh; Ahmad, Lisna; Saman, Widya Rahmawaty (Jambura Journal of Food Technology, 2024)
Starch is a carbohydrate which is a glucose polymer, and consists of amylose and amylopectin, for example corn and sorghum starch, but it still has several obstacles when used as raw materials in the food and non-food industries. If starch is cooked it takes a long time (requiring high energy), and the paste that is formed is hard and not clear. Therefore, starch modification was carried out by acid hydrolysis. This research was conducted to evaluate the effect of physical modification on pulut corn starch and sorghum starch using the Acid Hydrolysis method. The research was conducted at the Processing Laboratory, Department of Food Science and Technology, Faculty of Agriculture, Gorontalo State University in May 2024. The tools used were containers, glass beakers, ovens, water baths, blenders, sieves, plastic clips. The ingredients used are pulut corn flour, sorghum flour, distilled water, NaOH, and citric acid. The research design used a Completely Randomized Design (CRD). Test parameters include the size of starch granules. It is hoped that the research results will provide new insights in the development of starch technology based on corn and sorghum.